HAKIKAT TARBIYAH DAN TA’LIM DALAM AL-QUR’AN - Neha, Andi (LP2M Universitas PTIQ Jakarta, 2023)
Education is an important component in efforts to penetrate and transform human consciousness, attitudes and behavior. This paper aims to examine the nature of tarbiyah and taklim in the verses of the Koran. The research method used is a qualitative research method with a library study approach. In addition to examining the nature of tarbiyah and taklim in the Koran, this paper is also accompanied by a study of hadiths regarding tarbiyah and taklim. With various terminological studies, the research results show the difference between the nature of tarbiyah and taklim that the scope of the term al-ta'lim is more universal than the scope of the term al-tarbiyah